Strategies for Developing an e-Learning Curriculum for Library and Information Sciences (LIS) Schools in the Muslim World: Meeting the Expectations in the Digital Age - Hassan, Basri (Centre for Promoting Ideas, USA, 2013)
The emergence of information and communication technologies (ICTs), particularly,the Internet and other related technologies have brought about a fundamental and dramatic shift in the global educational system,which is changing by the day. This shift has manifested in the form of e- learning where ICT software and hardware are used as tools for teaching and learning. Thus, e-learning has become an integral part of the 21st century education and training which is adopted by different institutions. The paper discusses the concepts of e-learning and curriculum development. It also addresses the critical needs for developing an e-learning curriculum for LIS schools in the Muslim World. The discussion is rooted within the perspectives of the benefits of developing an e-learning curriculum that will provide accessibility to LIS education in the Muslim world; enhancing the quality of those programmes provided; as well as cost effectiveness of the e-learning programmes. Additionally, it presented the strategies for developing an appropriate e-learning curriculum for the LIS schools in the Muslim World. The paper equally discusses the challenges that could likely serve as stumbling block to such curriculum development strategy. It also suggested the potential solutions to such challenges. The paper concludes that e-learning has come to stay, and th at all efforts should be made by LIS schools in the Muslim world to ensure its full acceptance and adoption, if they are to become key players in the 21 st century LIS education arena